Analisis kemampuan guru dalam memanfaatkan media pembelajaran berbasis teknologi informasi dan komunikasi pada pembelajaran ipas kelas iv di sekolah dasar - Yustika, Arvenia; Istiyati, Siti; Adi, Fadhil Purnama (Didaktika Dwija Indria, 2025)
This research aims to describe teachers' abilities in utilizing Information and Communication Technology (ICT)-based learning media in class IV science learning at SDN Kleco I Surakarta. This research used descriptive qualitative approach with a case study type of research. Sampling in this study used a purposive sampling technique. Data collection techniques used tests, observation, interviews and document study. Data were obtained from class IVA, IVC and IVD teachers at SDN Kleco I Surakarta. The validity test technique used time triangulation and technique triangulation. The data analysis technique used is the Miles and Huberman model with stages of data collection, data reduction, data presentation, drawing conclusions and data verification. The results of this research are that theoretically teachers' knowledge regarding ICT learning media is included in the "Very Good" category with an average score of 100%, practically teachers' skills in using ICT learning media are in the "Very Good" category with an average score obtained amounted to 93.6%, and the teacher's ability to develop ICT learning media, the results are good because the teacher can choose, perfect and create it himself. However,there is still a need to improve teachers’ abilities in developing ICT learning media.